Hydrophilic closed-cell macroporous foam preparation by emulsion templating - Parın, Fatma Nur; Mert, E. Hilal (Elsevier, 2020)
Macroporous hydrophilic polyacrylate based closed-cell foams were synthesized by using glycerol 1,3diglycerolate diacrylate (GDG) as a starting monomer. Homopolymerization of GDG was conducted within the continuous phase of water-in-oil high internal phase emulsion (HIPE). In addition copolymerization of GDG with either 2-ethylhexyl acrylate (2-EHA) and 1,3-butanediol dimethacrylate (BDDMA) was investigated. Homopolymerization of GDG resulted in foams having cavities of 3.86 mm, while copolymerization with 2-EHA and BDDMA increased cavity sizes up to 74.12 mm and 135.93 mm, respectively. As compared to homopolymerized GDG foam, compression modulus of the foam prepared by copolymerizing GDG with BDDMA was increased 67%, while copolymerizing with 2-EHA caused a 66% of decrement in the compression modulus.(C) 2020 Elsevier B.V. All rights reserved.
Keywords: Porous materials; Emulsion templating; Closed-cell foam; Morphology; Mechanical properties; Thermal properties